HR Capability of Village Government Devices in Improving Public Services - Mimin Yatminiwati; Marsuhin Marsuhin; Emmy Ermawati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The purpose of this study was to determine the ability of the village government apparatus to mobilize human resources for public services in Jatisari village, Tempeh sub-district, and Lumajang district. The problem of this research is how the human resources of the village government are capable of providing public services in Jatisari village, Tempeh sub-district, and Lumajang district. This research method is descriptive and qualitative, looking for data related to the results of the performance of village government officials through direct interviews with the community in Jatisari village, Tempeh sub-district, and Lumajang district. In addition, researchers also collected data from print and electronic media related to the analysis of the human resource capabilities of village government officials in Jatisari village, Tempeh sub-district, and Lumajang district. The results of the study show that the technical skills of the Jatisari village government apparatus carry out their duties using techniques and supporting tools and procedures that are in accordance with the capabilities of a village government apparatus through the Internet. Human skills (human abilities) of the Jatisari village government apparatus motivate each other in carrying out tasks between devices that are carried out fairly and without regard for social status.Improving the ability of the Jatisari village government apparatus to carry out village government administration tasks includes: a) fostering employee discipline; b) education and training; c) work motivation; and d) career development.